Power Quality Performance Analysis of grid tied PV fed Parallel Pumping System under Normal and Vibrating Condition - Shankar V.K.A.; Umashankar S.; Sanjeevikumar P.; Mihet-Popa L.; Fedk V.; Ramachandaramurthy V.K. (Elsevier Ltd, 2023)
Centrifugal pumps; Electric power transmission networks; Power quality; Pumping plants; Pumps; Quality control; Variable speed drives; Vibrations (mechanical); Water quality; Appropriate control methods; Control techniques; Electrical power quality; Normal condition; Parallel pumping systems; Power quality parameters; Power quality performance; Vibrations; Electric power system control